Implementation of Law Number 23 of 2004 in Handling Domestic Violence Cases by the Deli Serdang City Police Resort - Prayuda, Chandra; Siregar, Taufik; Frensh, Wenggedes (Journal of Public Representative and Society Provision, 2025)
This study aims to analyze the application of Law Number 23 of 2004 concerning the Elimination of Domestic Violence (PKDRT) by the Deli Serdang City Resort Police (Polresta) in handling cases of domestic violence (KDRT). The method used is an empirical juridical approach with data collection through interviews, documentation studies, and direct observation. The results of the study show that the Deli Serdang Police have implemented procedural steps such as receiving reports, visum et repertum, and investigations. However, the implementation of the law has not been fully effective because informal mediation practices are still found that have the potential to reduce the deterrent effect for perpetrators and weaken legal protection for victims. Case data over the past five years (2020–2024) shows that physical violence is the most dominant form of domestic violence, while psychological and sexual violence is still rarely reported, indicating underreporting. The main obstacles in law enforcement include fear and dependence on victims, lack of witnesses, and family intervention. Judging from Lawrence M. Friedman's law enforcement theory, the weak structure and culture of law are obstacles in the implementation of the substance of the law. Meanwhile, from the perspective of legal protection theory, the authorities have not fully provided security and justice guarantees for victims. This study recommends the need to strengthen the victim protection system and the consistency of law enforcement without compromise to ensure legal certainty and justice.